(untitled) (Ágora de Heterodoxias, 2024)
This research arises from the situation that Ecuador experienced due to the covid-19 in the year 2020, in which the government implemented the Organic Law of Humanitarian Support. Due to this event, the research objective was to analyze the socio-economic impact of the reduction in working hours and wages on the quality of life of workers in the Ecuadorian private sector. Through the development of the conceptual, theoretical and legal framework, the most relevant issues are addressed in order to understand all the variables involved in the proposed research, which is research with a mixed approach: with regard to the quantitative aspect, the survey technique was applied to a sample of 384 employees while, for the qualitative aspect, interviews were conducted with 4 experts in the business area. The results of the research showed that the reduction of working hours and salary reduced the quality of life of workers in the Ecuadorian private sector, with reference to the working environment, there was an increase in stress and a decrease in motivation due to working more than the agreed hours, however, labour productivity remained at the same level